Fortunetelling as a Fraudulent Profession? - Verena Meier (Critical Romani Studies, 2023)
With the beginning of the Second World War the highest policy authority in the Nazi regime ordered that all fortunetelling female Sinti and Roma were to be incarcerated in concentration camps. This article traces the genesis of gendered antigypsyist motifs from the first written documentation on Sinti and Roma in Europe in the late Medieval period through the Enlightenment and the specialized discourse of criminology and penology in the nineteenth century. Furthermore, it analyzes both how the state apparatus criminalized fortunetelling as a fraudulent profession and how the criminal police under the Nazi regime implemented an order to incarcerate female Sinti and Roma by attributing the criminalized activity of fortunetelling.